Новые подходы к лечению синдрома задержки развития плода - Горбатовская, Э.В.; Шарашидзе, К.З.; Весич, Т.Л.; Сухина, Н.П. (Таврический медико-биологический вестник, 2011)
Проведено аналіз 90 спостережень вагітних з синдромом затримки розвитку плода (СЗРП), що показав патологічний вплив СЗРП на перебіг вагітності та формування перинатальної патології плода, патологічних змін ЦНС новонароджених. Встановлено, що основними патологічними чинниками формування перинатальної патології плода при СЗРП є імунопатологічні зрушення, а також метаболічні порушення. Показано, що включення Гемокорду в комплекс лікувально профілактичних заходів при СЗРП дозволяє нормалізувати імунореактивність вагітної і запобігти розвитку неврологічних порушень у новонароджених. The analysis is conducted 90 supervisions of pregnant with intrauterine fetal growth retardation This analysis demonstrated an influence of a complicated pregnancy and delivery course leading to a hypoxia on a formation of perinatal fetal CNS pathologies. The results obtained show that basic pathological factors of forming of perinatal damage during intrauterine fetal growth retardation are immunological disbalance and disorder of metabolic processes. It is shown that including of Hemocord in therapy-prevention complex of intrauterine fetal growth retardation and allows to normalize immunological status of pregnant and to prevent development of new-born neurological patology.